Computational study of blood flow through vortex generator integrated mechanical heart valve - Mohd Salleh, Nursyaira (2023)
Treatments for heart valve illness are being replaced by two types of prosthetics: bio-prosthetic heart valves (BHV) constructed from tissue material and mechanical heart valves (MHV) made of pyrolytic carbon. However, the replacement of the heart valve has several issues such as hemolysis, tissue overgrowth and thrombosis which still need improvement of the overall process. For MHV, the major complication is blood clotting, known as thrombosis and bleeding. MHV malfunction which lead to sudden death or stroke. The computational analysis was developed to study the blood flow through MHV equipped with VG. Thrombosis complications identified through non-physiological flow patterns such as pressure drop, recirculation, and wall shear stress (WSS). The result is validated with previous literature with percentage error of maximum velocity at central jet with 1.4% error. Results found that 1 mm triangular VG produced an optimum result with 25.13 % reduction of pressure drop compared to the absence of VG in laminar flow on idealized asymmetric aorta. Furthermore, three turbulence models, namely, Spalart Allmaras (SA), k-epsilon (k-ε), and Large Eddy Simulation (LES), were used to analyze the blood clotting potential in MHV with and without VGs under turbulence effect. The results found the LES turbulent model most suitable to capture unsteady solutions with rich coherent vortex shedding and providing 33.4 % lower WSS compared to the MHV without VGs. This method was also used for the anatomic aorta model with the same solver and including the VGs. The implication of VGs on the leaflet of SJM valve produced lower 15.33 % WSS and small recirculation zones by 7 % associated with lower platelet to be trapped inside anatomic aorta compared to the absence of VGs.